RISK AND INTENTION TO CONTINUE FINTECH PAYMENTS AMONG GEN Z AND MILLENNIALS - Arifah, Reni Nur; Khotimah, Putri Aryo Jelang Fitri; Kusumaningrum, Yetty Yuliani (Stability: Journal of Management and Business, 2024)
The purpose of this study is to examine how different risk types affect the sustainability of financial technology (fintech) service use among Indonesian Millennials and Generation Z. Financial, legal, security, operational, and social risks are among the risk categories examined, along with how they affect the overall risk of fintech and the decision to keep utilizing it for payments. 104 members of Indonesia's Generation Z and Millennial populations participated in an online survey that used a Likert scale to gather data. IBM SPSS Statistics software was used to do the quantitative analysis. The findings indicated that while operational and legal risks did not significantly affect fintech risk, financial, security, and social risks did. Furthermore, the risk of fintech had no